CLEANED: A tool for ex-ante assessment of environmental impacts of livestock production – A case study on dairy production in Tunisia - Hoek, Rein van der; Notenbaert, An Maria Omer; Musau, Emmanuel Mwema; Mukiri, Jessica; Paul, Birthe K. (2022)
In Tunisia, the dairy sector faces several productivity and competitiveness challenges, including a low processing rate of agricultural products, poor entrepreneurship among small farmers, and inadequate/unsustainable management of natural resources. For instance, water requirements for irrigation often exceed supply leading to irreversible depletion of aquifers.